Optimized Car Cooling System Using Solar Energy - Bassil Elie; Abou Haidar Gaby; Owayjan Michel; Achkar Roger (EPJ Web of Conferences)
Most of the time, people suffer from the high and low temperatures inside cars, throughout the various seasons. The cooling system used in cars does not allow proper air filtration and thus submits either cold or hot air depending on the external temperature. To avoid this problem, the air should be modulated to deliver the needed temperature. This raises the need to create a new system that can change the temperature in the car without damaging or affecting any other parts. This paper consists of integrating semiconductors that can affect the ability to light and heat. The connection of the semiconductors to a solar panel allows the conversion of the sunlight into electricity. Adding a fan to the system is crucial because colder air can be drawn into the car from the outside and expels air from the inside. This addition can also cool the intimate car atmosphere by moving air across a heat sink. After the structure had been created, many experiments are tested. These tests reflect good performance under temperature changes causing different incoming currents related to time.